Theodicy between Apology and Cosmology: An Examination of Contemporary Islamic Perspectives on Evil and Suffering Amidst Global Crisis - Hureyre Kam (22030973) (2024)
In the realm of theological inquiry, few subjects have sparked as much contemplation, debate, and intellectual pursuit as the question of theodicy. As humanity grapples with the profound realities of suffering, evil, and the existence of an omnipotent and benevolent deity, theodicy emerges as a vital arena where philosophy, theology, and ethics intersect. At the heart of this complex discourse lies a fundamental inquiry: how can a benevolent and all-powerful God coexist with the presence of suffering and malevolence in the world? It is within this intricate tapestry of paradoxes that the edited volume under review seeks to navigate, offering readers a compelling exploration of theodicy’s multifaceted dimensions with a particular focus on the effects of the COVID-19 pandemic. Other Information Published in: Journal of Islamic Ethics License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1163/24685542-20240010 Volume and issue information: Vol 8 No. 1-2 (2024): December 2024